Gambaran histologi pankreas tikus Wistar yang diberi ekstrak daun Binahong setelah diinduksi sukrosa - Tahulending, Trianingsi P.R.; Kaseke, Martha Marie; Angmalisang, Elvin Clara (JURNAL KEDOKTERAN KOMUNITAS DAN TROPIK, 2019)
Background: Sucrose If consumed in excess could increase blood glucose level cause contains high amount of glucose. Binahong leaves are used empirically by the community. Binahong leaf extract that contain bioactive substance of saponin and flavonoid as antioxidants. This study aims to find out the histological description of wistar pancreas after sucrose induced, after sucrose induced and given binahong leaf extract simultaneously and given binahong leaf extract after sucrose induced. Methods : This was an experimental study using the post-test only control group design. As subjects, we used 20 male wistars, 2 months old with an average body weight of 180 gr divided into 4 groups: negative control group (N) without intervention in 14 days, termination in 15 day; (P1) containing sucrose induced in 14 days, termination in 15 day; (P2) containing sucrose induced and given binahong leaf extract simultaneously in 14 days, termination in 15 day, (P3) containing of sucrose induced in 14 days and given binahong leaf extract for 14 days, termination in 29 day. Results: in group (N) showed a picture of normal langerhans islet, (P1) there was an increase in the number and size of langerhans islet from small to moderate, (P2) there was an increase in the number and size of langerhans islet from small, large to very large, (P3) there was an increase in the number and size of langerhans islet from small to very large. Conclusion: Histological description of wistar pancreas in groups (N): normal and in groups (P1), (P2), (P3) hyperplasia occurs increase in the number and size of langerhans islet : (P1) small to moderate; (P2) small, large to very large; (P3) small to very large.